Genomic traits of multidrug resistant enterotoxigenic Escherichia coli isolates from diarrheic pigs - Hu, Jiameng; Li, Junlin; Huang, Xiaobo; Xia, Jing; Cui, Min; Huang, Yong; Wen, Yiping; Xie, Yue; Zhao, Qin; Cao, Sanjie; Zou, Likou; Han, Xinfeng (Frontiers in Microbiology, 2023)
Diarrhea caused by enterotoxigenic Escherichia coli (ETEC) infections poses a significant challenge in global pig farming. This study aimed to identify and characterize 19 ETEC isolates from fecal samples of diarrheic pigs obtained from large-scale farms in Sichuan Province of China, using whole-genome sequencing and bioinformatic analysis. Antimicrobial susceptibility testing indicated significant resistance against cefotaxime, ceftriaxone, chloramphenicol, gentamicin, tetracycline, ampicillin, florfenicol and sulfadiazine. In contrast, high level of susceptibility was observed to amikacin, imipenem, and cefoxitin. The investigation revealed remarkable genetic diversity among the isolates, with serotypes O22:H10, O163 or OX21:H4 and O105:H8 being the dominant serotypes. Further analysis of antimicrobial resistance genes and virulence factors unveiled 53 resistance genes and 13 categories of 195 virulence factors. The presence of tet(X4) in some isolates raised concerns of public health. The investigation revealed that the ETEC isolates exhibited the potential ability to produce either heat-stable enterotoxin (ST) alone or both heat-labile enterotoxin (LT) and ST simultaneously. In addition, this observation highlighted the role of various virulence genes, including eltA, eltB, eltIAB-4, estap-STa1, estap-STa6, estb-STb1 and astA, in potential toxin 2 production. Notably, the presence of STa1 and STa6 were linked to human disease. Furthermore, the presence of four hybrid ETEC/STEC isolates harboring Shiga-like toxin-related virulence factors, namely stx2a, stx2b, and stx2e-ONT-2771, was identified. IncF plasmids carrying multiple antimicrobial resistance genes were prevalent, and a hybrid ETEC/STEC plasmid was detected, highlighting the role of plasmids in hybrid pathotype emergence. These findings emphasized the multidrug resistance and pathogenicity of porcine-origin ETEC strains and the potential risk of epidemics through horizontal transmission of drug resistance, which is crucial for effective control strategies and interventions to mitigate the impact on animal and human health.